Qualitative and quantitative gas chromatography-mass spectrometry analysis of the principal toxic constituents of some South African plants in human biological fluid - Laurens, Johannes B. (University of Pretoria, 2021)
Dissertation (MSc (Chemistry))--University of Pretoria, 2021.